Analisa Analisa Pemilihan Sistem Moda Transportasi Antara Bus Angkutan Kota Dengan Kereta Api Rute Medan Tanjung Balai - Irma Dewi (Cered Indonesia Institute, 2020)
The movement activity from Medan City to Tanjung Balai City is a fairly dense movement. The movement between the two cities can be served by several modes of transportation including trains and intercity transport buses (KUPJ, KUPJ TOUR, Sartika). The purpose of this study is to find out which public transportation is most interested in by the public before and after changes in the train system with city transportation buses, as well as analyze the variables of destination, consideration, and service of the Medan Tanjung Balai route. Based on the results of the analysis between passenger data from agencies and the results of field questionnaires, passengers prefer trains over intercity transport buses. This is due to the efficiency of fast train mileage compared to intercity transport buses. From the results of independent variables (goals, considerations, services) positively and significantly give a good influence to users of rail transport and city transport buses.